The Dynamics of Conflict, Development Assistance and Peace-Building : Sri Lanka 2000-05 - World Bank (Washington, DC, 2012)
Significant transformations in the socio-political and economic landscape of Sri Lanka in recent years encouraged five development partners-World Bank, Asia Foundation, and the governments of the United Kingdom, Netherlands and Sweden to collaborate on a conflict assessment in 2005. This reflects a growing trend in the development partner community of combining efforts, pooling resources, and taking advantage of comparative strengths to engage in conflict analysis exercises. The multi-donor conflict assessment revisits the underlying structures of conflict, identified in the previous conflict assessment, and explores the current dynamics of conflict factors with a particular focus on the peace process and international engagement. This note presents key findings of the assessment, in particular, the approaches supported by development partners in Sri Lanka. While this is drawn solely from the Sri Lanka experience, it is likely to have a broad relevance to many such countries.